2013
DOI: 10.1007/s11102-013-0498-9
|View full text |Cite
|
Sign up to set email alerts
|

Hypophysitis due to IgG4-related disease responding to treatment with azathioprine: an alternative to corticosteroid therapy

Abstract: Hypophysitis due to IgG4-related disease usually demonstrates prompt response to corticosteroids. This case highlights the need to image promptly after starting treatment to exclude an enlarging pituitary mass despite corticosteroid treatment. Alternative therapy with azathioprine can result in marked improvement. It should be remembered that IgG-4 related hypophysitis is part of a multi-organ disease.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
32
1
6

Year Published

2014
2014
2023
2023

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 68 publications
(40 citation statements)
references
References 28 publications
1
32
1
6
Order By: Relevance
“…But in some cases, the enlargement of pituitary mass was not improved even though glucocorticoid administration resulted in a reduction of serum IgG4. Caputo et al [28] recently reported alternative therapy with azathioprine resulted in marked improvement in such a case. In the present case, PSL markedly reduced serum IgG4 levels and the size of pituitary mass and stalk along with partial improvement of anterior pituitary function.…”
Section: Case Reportmentioning
confidence: 94%
“…But in some cases, the enlargement of pituitary mass was not improved even though glucocorticoid administration resulted in a reduction of serum IgG4. Caputo et al [28] recently reported alternative therapy with azathioprine resulted in marked improvement in such a case. In the present case, PSL markedly reduced serum IgG4 levels and the size of pituitary mass and stalk along with partial improvement of anterior pituitary function.…”
Section: Case Reportmentioning
confidence: 94%
“…measured prior to corticosteroid administration was 950.5G872.3 mg/dl in 11 cases, which was much higher than that for all cases (595.0G 729.1 mg/dl), suggesting that glucocorticoid therapy decreases serum IgG4 concentrations. Caputo et al (21) reported a case in which serum IgG4 concentration was reduced after prednisolone administration, which again indicates the importance of measuring IgG4 concentrations before steroid replacement therapy. The involvement of various organs was noted throughout the clinical course, with retroperitoneal fibrosis being the most common form (38%), followed by interstitial pneumonia (eight cases, 28%), Mikulicz's disease and AIP (seven cases, 24%), and lymph node swelling (five cases, 18%).…”
Section: European Journal Of Endocrinologymentioning
confidence: 97%
“…Leporati et al (7), the first to report IgG4-related hypophysitis in Caucasian patients, reviewed the published literature and proposed diagnostic criteria on the basis of findings of 11 cases that were analyzed. Although the first IgG4-related hypophysitis case was described in 2004 (3), only six histologically proven cases have been reported (3,4,7,8,9,10,11,12,13,14,15,16,17,18,19,20,21).…”
Section: Introductionmentioning
confidence: 99%
“…The male-to-female ratio is 2.9:1 [6]. Serum IgG4 measured before giving steroids is much higher than that following steroids, as shown by Caputo et al [7].…”
Section: Discussionmentioning
confidence: 73%
“…Caputo et al reported relapse in a case of IgG4-related hypophysitis, after treatment with a high dose of prednisolone, who was then successfully treated with azathioprine [16].…”
Section: Discussionmentioning
confidence: 99%